Adaptive zone, Petersen-type communities, geographical range and ecological niche. Report 1. Defnitions and relations of the concepts - I. V. Volvenko (Известия ТИНРО, 2018)
Defnition of the term adaptive zone (AZ) is amended. The Petersen-type communities (PC) are not communities in every sense of the word. They are just the areas within which the same species prevail in their abundance. An accounting gear used for identifcation of PC must be suited for catching of the most abundant species. All dominant species must be represented in the lists, regardless of whether they are seasonal or permanent components of population. Only one factor (either number of individuals or biomass) has to be used for species abundance comparison. For recognition and naming of several PC, the same number of the dominant and subdominant species should be used. Under the abovementioned conditions, if this number is equal to 1 — this method selects nothing more than AZ, which are the elementary PC. The fundamental ecological niche (EN) of a species includes its realized AZ — the real space actually coincides with its geographical range (GR). The GR is situated inside the EN, and the realized AZ is a part of GR. The GR (and sometimes EN) of different species can be partially or fully overlapped, but their AZ cannot be overlapped. Each AZ is compliant with a certain species, but not each species is compliant with AZ. AZ are available to the most dominant species and the size of AZ may serve as one of simple measures of the species capability for survival or success in their struggle for existence, and corresponds to portion of total ecological capacity of the environment used by the species. The interiors of the species GR may contain from zero to several AZ, both of this and other species. The interiors of the species AZ also contain parts of GR of other species having similar requirements to the environment (prey, predators, parasites, competitors, symbionts, and other biotic habitat factors). Potential AZ may be located both inside and outside the real GR of a species, but only within its fundamental GR. The potential AZ can be realized by changing the environmental conditions or passing through existing barriers of distribution. Transformation of potential AZ into a realized one can cause an ecological catastrophe if it breaks the existing balance and leads to signifcant redistribution of the shares of total ecological capacity available for species. But even signifcant changes in the ratios of GR and AZ of species will not cause catastrophic consequences in conditions of abundant vital resources, if ecological capacity of the environment is not flled and packing density of EN is low. Changes in the environment, as well as ontogenetic, migratory, succession and evolutionary processes cause changes in ratio of abundance between different species, including mass ones, that leads to variability of their AZ. Number, sizes, shapes, location of the AZ change progressively, both on the actual and geological time scales, and cyclically in accordance with circadian, seasonal and perennial rhythms. Therefore AZ, as well as GR, EN and communities, should be studied in dynamics and in connection with changes in the environment. Defnitions of the main terms are presented in a Supplement.